2016
DOI: 10.1017/s1466252316000013
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of calves against common respiratory viruses in the face of maternally derived antibodies(IFOMA)

Abstract: Vaccination of calves in the face of maternal antibodies (IFOMA) often does not result in seroconversion as maternally derived immunity interferes with the activation of adequate antibody responses to vaccination; however, it can prime T and B cell memory responses that protect calves against clinical disease when maternal immunity has decayed. The activation of B and T cell memory responses in calves vaccinated IFOMA varies and is affected by several factors, including age, level of maternal immunity, type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
(65 reference statements)
1
18
0
1
Order By: Relevance
“…While some studies have suggested that MDA can prevent RSV infection ( 72 , 73 ), it is known that RSV severe disease can occur in presence of MDA in both calves ( 51 , 74 ) and humans ( 75 78 ). Although the outcome of vaccination is shaped by multiple factors, it is well documented that MDA can interfere with generation of active immunity in vaccinated calves ( 79 81 ). Successful strategies to overcome this major hurdle include mucosal vaccination and triggering cell-mediated immune mechanisms, i.e., by adjuvanted parenteral vaccines ( 70 , 82 ) The BCG vector employed in this formulation is well recognized as a highly immunogenic vaccine or adjuvant, being a potent stimulator of Th1 immunity in adults and newborns, triggering antigen-specific CD4 + and CD8 + T cells ( 83 – 85 ) Efficient cell-mediated immunity and IFN-γ secretion have been observed after s.c. BCG vaccination of calves as early as 8 h after birth ( 86 ), and one-week-old BCG-vaccinated calves show cellular and IFN-γ responses to PPD-B comparable to adult animals ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that MDA can prevent RSV infection ( 72 , 73 ), it is known that RSV severe disease can occur in presence of MDA in both calves ( 51 , 74 ) and humans ( 75 78 ). Although the outcome of vaccination is shaped by multiple factors, it is well documented that MDA can interfere with generation of active immunity in vaccinated calves ( 79 81 ). Successful strategies to overcome this major hurdle include mucosal vaccination and triggering cell-mediated immune mechanisms, i.e., by adjuvanted parenteral vaccines ( 70 , 82 ) The BCG vector employed in this formulation is well recognized as a highly immunogenic vaccine or adjuvant, being a potent stimulator of Th1 immunity in adults and newborns, triggering antigen-specific CD4 + and CD8 + T cells ( 83 – 85 ) Efficient cell-mediated immunity and IFN-γ secretion have been observed after s.c. BCG vaccination of calves as early as 8 h after birth ( 86 ), and one-week-old BCG-vaccinated calves show cellular and IFN-γ responses to PPD-B comparable to adult animals ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vacunar cuando existen anticuerpos maternos circulantes se considera un problema de protección inmune. Esta situación se conoce como anticuerpos en fase materna (In face of maternal antibody, IFOMA, por sus siglas en inglés) (Chamorro et al, 2016). Esto pudo impedir observar diferencias entre inmunidad pasiva y activa, porque la vacuna muerta no pudo inducir una respuesta humoral dado que existían anticuerpos maternos; asimismo, es necesario tener en cuenta el bloqueo al desarrollo de inmunidad en una cría con alta protección calostral, como sucede en los mamíferos nacidos de placentación sindesmocorial (Windeyer y Gamsjäger, 2019), lo cual explicaría la ausencia de diferencias para el T4, que recibió una dosis vacunal en una edad en la cual no hay respuesta del sistema inmune (Sherwin y Down, 2018).…”
Section: Fuente: Autoresunclassified
“…In practice, inducing protective immunity against respiratory pathogens through vaccination of young calves may be difficult, due both to immune system immaturity and to the potential interference of MDA 5 6. Intranasal modified live vaccines (MLV) induce both an adequate systemic response and at the same time a local antibody response 7.…”
Section: Introductionmentioning
confidence: 99%